Hepatocellular Carcinoma: Does the Background Liver With or Without Cirrhosis Matter?. Issue 2 (20th September 2021) - Jain, Anisha; Mazer, Benjamin; Deng, Yanhong; Ciarleglio, Maria; Jain, Dhanpat; Taddei, Tamar; Zhang, Xuchen
Abstract: Objectives: The pathologic differences between hepatocellular carcinoma (HCC) arising in noncirrhotic and cirrhotic livers have not been well studied. Methods: We performed a retrospective analysis of 378 HCC cases (95 in noncirrhotic, 283 in cirrhotic livers) from pathology archives (2010-2017). Results: Patients without cirrhosis were more likely to have hepatitis B (13.68% vs 2.83%, P  < .001) or no known liver disease (30.53% vs 4.24%, P  < .001), while hepatitis C was more common in patients with cirrhosis (65.72% vs 30.53%, P  < .001). HCCs in noncirrhotic livers were larger in size ( P  < .001); were more likely to have a macrotrabecular histologic pattern (13.68% vs 4.95%, P  < .01); were more likely to have fibrolamellar (3.16% vs 0%, P  = .02), macrotrabecular-massive (13.68% vs 6.01%, P  = .03), and clear cell (16.84% vs 6.71%, P  < .01) subtypes; have a higher histologic grade ( P  < .01); be anaplastic tumor cells ( P  < .001); have a higher rate of vascular invasion ( P  < .01); and have a higher tumor stage ( P  = .04). Conclusions: The findings indicate that HCCs in noncirrhotic livers demonstrate a larger tumor size; have a more macrotrabecular histologic pattern; have fibrolamellar, macrotrabecular-massive, and clear cell subtypes; have a higher tumor grade and stage; have a higher rate of vascular invasion; and have more anaplastic tumor cells compared with cirrhotic livers. Further studies to explore different pathways that promote oncogenesis in noncirrhotic livers are needed to better understand the pathogenesis of HCC.